Foreign Policy, Public Diplomacy, and Social Media: Observing Indonesian Missions Practice - Intentilia, Anak Agung Mia (Nation State: Journal of International Studies, 2023)
This paper observes the practice of Indonesian Missions abroad in conducting public diplomacy via social media. The research question is how do the Indonesian Missions abroad utilize social media to connect with the public and to support Indonesia’s foreign policies? This paper uses a descriptive qualitative method with primary and secondary data. Primary data are gathered by observing @indonesiainjeddah and @desrapercaya on Instagram. Secondary data are compiled by using literature studies of articles from reputable journals. There are three main findings of this paper. Firstly, the Ministry of Foreign Affairs of Indonesia emphasizes the importance of digital technology for diplomacy, proven by the Social Media Awards to appreciate the efforts in disseminating Indonesia’s foreign policy overseas. Secondly, the Indonesian Consulate in Jeddah, @indonesiainjeddah, has utilized social media account to disseminate Indonesia’s foreign policy, covering economic and health diplomacy, diplomacy for citizens’ protection, and Indonesia’s G20 Presidency. Thirdly, Ambassador Desra Percaya, @desrapercaya, has contributed to disseminating the foreign policy of Indonesia in the context of economic diplomacy, sports diplomacy, and the regional issue of ASEAN, with the additional element of cultural diplomacy. These findings confirm that Indonesia’s public diplomacy can be conducted using social media, to further promote Indonesia’s foreign policy.